2011
DOI: 10.1021/ma102825r
|View full text |Cite
|
Sign up to set email alerts
|

Highly Branched Polypropylene via Li+-Catalyzed Radical Polymerization

Abstract: b S Supporting Information W hile radical polymerization techniques are well suited for polar monomers, they are not used to polymerize simple R-olefins as the allylic hydrogens on the latter are subject to chain transfer in the presence of a reactive propagating radical. 1 Thus, with the exception of ethylene produced commercially at very high pressures and temperatures (and a few reports of propylene under similar intense conditions 2,3 ), only short oligomers of simple alkenes such as propylene or 1-hexene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…Nevertheless, only low‐molecular‐weight oligomers with M n < 1000 were detected as a result of radical polymerization of all tested 1‐alkenes at elevated temperatures, regardless of the initiator used, and for these longer alkenes we were not able to reproduce the initial results 1. This contrasts with the reproducibility found for the short alkenes, isobutylene4 and propylene 5…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Nevertheless, only low‐molecular‐weight oligomers with M n < 1000 were detected as a result of radical polymerization of all tested 1‐alkenes at elevated temperatures, regardless of the initiator used, and for these longer alkenes we were not able to reproduce the initial results 1. This contrasts with the reproducibility found for the short alkenes, isobutylene4 and propylene 5…”
Section: Discussioncontrasting
confidence: 58%
“…With nonoxidizing initiators, this alkene yields a previously unknown hyperbranched polymer with molecular weights in excess of 2 × 10 4 g/mol, and with oxidizing initiators, it yields a mixture of the same hyperbranched polymer with ordinary linear polyisobutylene with molecular weights up to 5 × 10 4 g/mol, even at temperatures as high as 80 °C. In another recent investigation,5 it was found that propylene also readily forms a very highly branched polymer, with molecular weights up to 3 × 10 4 g/mol. Moreover, copolymers of isobutylene and ethyl acrylate were synthesized by radical copolymerization using the same Li[CB 11 Me 12 ] activator 2, 4…”
Section: Introductionmentioning
confidence: 97%
“…In the absence of the initiator or of the lithium salt, or in the presence of a radical inhibitor or a lithium complexing solvent, polymerization did not take place. 162,163 A closer look at the polymers formed from propylene (very highly branched, molar mass ∼30000 g•mol −1 ), 164 higher alkenes (molar mass below 1000 g•mol −1 ), 165 and most of all, isobutylene (very highly branched, see below), 161,165,166 as well as the copolymerization of isobutylene with ethyl acrylate (with up to ∼50 mol % IB content, highly branched, molar mass ∼30−50000 g•mol −1 ), 149,165 gradually revealed that it is difficult to reproduce some of the initially reported molar mass values. It ultimately became clear that the yields, molar masses, and at times even the structures of the polymers were a very sensitive function of the composition of the catalytic solution and that painstaking control was required to obtain reproducible results.…”
Section: Problemsmentioning
confidence: 99%
“…Catalysis with 1 can also be used for radical copolymerization of IB with ethyl acrylate. , Most recently we have examined in more detail the radical polymerization of propene, which produces highly branched polypropylene . In contrast, 1-hexene and 1-octene yield only relatively low molecular weight oligomers under the conditions used recently .…”
Section: Introductionmentioning
confidence: 99%
“…3,8 Most recently we have examined in more detail the radical polymerization of propene, which produces highly branched polypropylene. 9 In contrast, 1-hexene and 1-octene yield only relatively low molecular weight oligomers under the conditions used recently. 10 Admittedly, until the detailed composition of the presumably colloidal catalytic solutions containing 1 in solvents of low polarity is better understood, it will be difficult to control these polymerization reactions.…”
mentioning
confidence: 96%